Diversidade genética estimada com marcadores ISSR em população natural de cambuizeiro (Myrciaria tenella O. Berg) - Santana, Josefa Grasiela Silva (2016)
Belonging to the Myrtaceae family, cambui tree (Myrciaria tenella O. Berg) is native of Brazil. The Molecular characterization is one of the most used tools for potential species because infers about level of diversity between individuals. Analysis of genetic diversity are critical to the direction of the strategies needed to build and maintain a germplasm. The objective of this work was to estimate the genetic diversity in a natural population of cambui using molecular markers ISSR. The provider of plant material used is a natural population, in Private Natural Heritage Reserve (RPPN) in part of the Experimental Field of Embrapa Coastal Tablelands, in the municipality of Itaporanga d'Ajuda, SE. Young leaves of each individual were collected for ADN extraction and analysis of PCR-ISSR (Simple Sequence Repetitive Internal). Were tested 30 primers and selected 10 for the analysis. The use of these primers resulted in 71 fragments with 98.3% of polymorphism. The similarity of the individuals ranged between 0.30 and 0.92, with the most similar C17 and C13 and more distant, C1 and C41. Through UPGMA was possible to identify six distinct groups. The information obtained will be used for conservation of these genetic resources, direct exchange of germplasm and / or training of ex situ collections and assist in future work with the species.